The Management of Lower Ureteric Stones: A Comparison of Silodosin and Extracorporeal Shock Wave Lithotripsy with Regard to Efficacy and Safety - Zakir Hussain Rajpar, Kashifuddin Qayoom Soomro, Shoukat Ali Mughal, Syed Azhar Hussain, Aijaz Shaikh, Afhan Qayoom Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the efficacy and safety of silodosin versus extracorporeal shock wave lithotripsy for the management of lower ureteric stone. Study design: Randomized controlled trial Place & Duration of Study: Conducted at Liaquat University of Medical and Health Sciences Jamshoro during from the period September 2022 to August 2023. Methods: Total 110 patients of either gender with ureteric stone were included. All the cases were equally divided in to two groups i.e. Group I in which patients received extracorporeal shock wave lithotripsy and group II patients were given 8mg silodosin orally for 3 weeks and advised to discontinue if stone passage. Results: Majority of patients were male in Group I and II 36 (65.45%) and 37 (67.27%). Mean age in group I was 37.42+7.24 years while in group II, the mean age was 36.55+6.87 years. The success rate in term of clearance of stones, Group I had 72.73% while Group II had 90.91%. The difference was statistically significant p-value 0.012. Complications were more in ESWL group as compared to silodosin group p-value <0.05. Conclusions: The silodosin is more efficacious and safe than extracorporeal shock wave lithotripsy for elimination of ureteric stones. Keywords: Ureteric Stone, Silodosin, Extracorporeal shock wave lithotripsy